Lifelong Learning Center incubator for learning and livelihood - Reyes, Joyce Alyssa D. (College of Architecture, University of the Philippines Diliman, 2020)
Home to several institutions and numerous knowledge resources, Quezon City envisions itself to become the Knowledge Capital of the Country. In materializing this role, an area within districts 1,3 and 4 of QC known as the CBD Knowledge Community District bears the most crucial role. Economic activity within the area, however, primarily caters to the middle and upper-class citizens- those are financially competent enough to attain education in recognized schools and universities. By placing highly needed skill development programs in formal educational institutions, low-income earners are further pushed away from the knowledge community. There is a divide between the knowledge entities and "other" people who reside within the community - showing an evident demonstration of exclusivity and detachment. In response, this thesis aims to deinstitutionalize learning through the Lifelong Learning Center. Lifelong learning (LL) or continuous learning and development of skills and knowledge ensures the quality and capabilities of the labor pool. As such, learning opportunities should be present and pursued throughout an individual's lifetime. The Lifelong Learning Center seeks to provide a platform for underserved members to impact the growth of the city through contextualized learning and livelihood. By providing an inclusive and immersive space for out-of-school youths and adults to learn, train and work, the facility becomes instrumental in carrying out social process throughout the development of work and life skills. Integration of livelihood spaces within learning and training settings encourages cooperation among the agencies, stakeholders, and the community resulting in a more coherent flow and exchange of knowledge. Finally, the research aims to explore a more sustainable approach to the development of work life by showing that learning is not only confined within the walls of a classroom but is present in all our daily encounters.